Local buckling of rectangular concrete-filled steel tubular columns with binding bars under eccentric compression. Issue 10 (July 2020) - Wan, Jun; Cai, Jian; Long, Yue-Ling; Chen, Qing-Jun
Based on the energy method, this article presents a theoretical study on the elastic local buckling of steel plates in rectangular concrete-filled steel tubular columns with binding bars subjected to eccentric compression. The formulas for elastic local buckling strength of the steel plates in eccentrically loaded rectangular concrete-filled steel tubular columns with binding bars are derived, assuming that the loaded edges are clamped and the unloaded edges of the steel plate are elastically restrained against rotation. Then, the experimental results are compared with these formulas, which exhibits good agreement. Subsequently, the formulas are used to study the elastic local buckling behavior of steel plates in rectangular concrete-filled steel tubular columns with binding bars under eccentric compression. It is found that the local buckling stress of steel plates in eccentrically loaded rectangular concrete-filled steel tubular columns with binding bars is significantly influenced by the stress gradient coefficient, width-to-thickness ratio, and the longitudinal spacing of binding bars. With the decrease of width–thickness ratios or the longitudinal spacing of binding bars or with the increase of the stress gradient coefficient, the local buckling stress increases. Furthermore, the influence of the longitudinal spacing of binding bar is more significant than the stress gradient coefficients. Finally, appropriate limitation for depth-to-thickness ratios ( D / t ), width-to-thickness ratios ( B / t ), and binding bar longitudinal spacing at various stress gradient coefficients ( α 0 ) corresponding to different cross-sectional aspect ratios ( D / B ) are suggested for the design of rectangular concrete-filled steel tubular columns with binding bars under eccentric compression.